Business Marketing Strategy Analysis as a Business Competition Strategy in the Cafe Business: A Study of Cafe Janaloka - Nur Afika Fitriani; Dewi Sinta Puspitasari; Yaumi Rohmah; Ahmad Gozi; Sudarmiatin Sudarmiatin (Jurnal Bintang Manajemen, 2024)
In an increasingly competitive business world, marketing strategies are essential for success, especially for coffee shop businesses. In recent decades, coffee shops have increased in popularity worldwide. This study focuses on the segmenting, targeting, and positioning (STP) strategies used by Cafe Janaloka. The method used in this study is a qualitative research case study. Which is a research approach used to explore an in-depth understanding of a particular phenomenon, in a real and specific context. The technique used is to conduct interviews. The results of this study are the success of maintaining its existence amidst tight competition through the implementation of effective marketing strategies. The segmentation process is carried out based on geographic, demographic, and psychographic factors, with the main focus on students. Targeting is directed at those who come to the cafe to hang out, and work on assignments with friends, or community partners. Cafe Janaloka's positioning is strengthened through coffee with quality ingredients which are black coffee produced by ourselves, as well as the existing menu, and what has been done by Janaloka Cafe is the creation of black ginger coffee. This study shows the importance of in-depth market analysis to improve the competitiveness of MSMEs, especially through the implementation of a well-planned STP strategy.